Comparison of temporalis fascia muscle and full-thickness cartilage grafts in type 1 pediatric tympanoplasties - Yegin,Yakup (2016)
Abstract Introduction: Various graft materials have been used to close tympanic membrane perforations. In the literature, there are few studies in pediatric populations comparing different graft materials. To our knowledge, there is no reported study that measured the thickness of the tragal cartilage in pediatric tympanoplasties. The tragal cartilage is not of uniform thickness in every patient. Objective: To compare anatomical and functional outcomes of temporalis fascia muscle and full-thickness tragal cartilage in type 1 pediatric tympanoplasties. Methods: In total, 78 patients (38 males, 40 females; average age 10.02 ± 1.98 years; range, 7-18 years) who underwent type 1 tympanoplasties in our clinic were included. Demographics, anatomical, and functional outcomes were collected. Temporalis fascia muscle and tragal cartilage were used as graft materials. Tragal cartilage was used without thinning, and the thickness of tragal cartilage was measured using a micrometer. Anatomical and functional outcomes of cartilage and fascia were compared. Audiometric results comparing the cartilage and fascia groups were conducted at 6 months, and we continued to follow the patients to 1 year after surgery. An intact graft and an air-bone gap ≤ 20 dB were regarded as a surgical success. Results with a p-value < 0.05 were considered statistically significant. Results: The graft success rate was 92.1% for the cartilage group compared with 65.0% for the temporal fascia group. In the fascia group, the preoperative air-bone gap was 33.68 ± 11.44 dB and postoperative air-bone gap was 24.25 ± 12.68 dB. In the cartilage group, the preoperative air-bone gap was 35.68 ± 12.94 dB and postoperative air-bone gap was 26.11 ± 12.87 dB. The anatomical success rate in the cartilage group was significantly better than that for the fascia group (p < 0.01). There was no statistically significant difference in functional outcomes between the fascia and cartilage groups (p > 0.05). The average thickness of tragal cartilage in the pediatric population was 0.693 ± 0.094 mm in males and 0.687 ± 0.058 mm in females. Conclusions: Our data suggest that the anatomical success rate for a cartilage tympanoplasty was higher than for a fascia tympanoplasty. Functional results with cartilage were not different than with fascia, even though we did not thin the tragal cartilage. However, further studies should focus on the interaction between the thickness of the tragal cartilage and the tympanoplasty success rate.